A Belgian Randomized Trial in Hepatitis C Virus-Infected Patients with Persistently Normal Alanine Aminotransferase - Okyay Elkilic; Philippe Langlet; Michael Adler; Chantal De Galocsy; Isabelle Colle; An Reekmans; JeanPierre Mulkay; Hans Van Vlierberghe; Nathalie Boon; Geert Robaeys; Luc Lasser (Global Journal of Clinical Virology - Peertechz Publications, 2016)
Persistently normal alanine aminotransferase (PNALT) is present in 30 to 40% of chronic hepatitis patients and it is generally accepted that they have no liver damage. However, some studies suggest that there are some degrees of mild to moderate histological liver damage. We evaluated the fibrosis stage and the virological outcome in treated patients with PNALT.                                                     We collected HCV-positive patients with normal liver enzymes in a Belgian multicenter prospective randomized study between 2002 and 2006. They had fibrosis with at least F1 in Metavir score. Patients were followed for two years. They were divided in two groups. Group 1 (n=17) were patients treated by Pegylated Interferon alfa-2b (Pegintron) plus ribavirin (Rebetol). Group 2 (n=18) received no treatment and were used as a control group for 48 weeks. The sustained virological response (SVR) was 41% (7/17). The SVR in our study is equivalent for patients with elevated ALT levels. We also evaluated the evolution of the transaminases during treatment in group 1 patients. We observed a diminution of the already normal ALT and AST values, in patients who were treated. In our opinion there is no other publication that showed this evolution of the transaminases during treatment of HCV. With the knowledge that in our study, the patients showed a minimal degree of fibrosis even with normal liver enzymes, we agree with the findings of some authors who suggest to lower normal limit of the transaminases.